2019
DOI: 10.5194/tc-13-1349-2019
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification of the multi-centennial response of the Antarctic ice sheet to climate change

Abstract: Abstract. Ice loss from the Antarctic ice sheet (AIS) is expected to become the major contributor to sea level in the next centuries. Projections of the AIS response to climate change based on numerical ice-sheet models remain challenging due to the complexity of physical processes involved in ice-sheet dynamics, including instability mechanisms that can destabilise marine basins with retrograde slopes. Moreover, uncertainties in ice-sheet models limit the ability to provide accurate sea-level rise projections… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
134
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(162 citation statements)
references
References 115 publications
(209 reference statements)
16
134
0
Order By: Relevance
“…Under RCP2.6, DeConto and Pollard's modeling experiment produced virtually no net Antarctic contribution to global mean sea level by 2100, with only a 20 cm rise by 2500. Another study found that the RCP2.6 scenario prevented collapse of the WAIS regardless of uncertainties in model parameters (Bulthuis et al, 2019).…”
Section: Commitment To Loss Of the Greenland And West Antarctic Ice Smentioning
confidence: 99%
“…Under RCP2.6, DeConto and Pollard's modeling experiment produced virtually no net Antarctic contribution to global mean sea level by 2100, with only a 20 cm rise by 2500. Another study found that the RCP2.6 scenario prevented collapse of the WAIS regardless of uncertainties in model parameters (Bulthuis et al, 2019).…”
Section: Commitment To Loss Of the Greenland And West Antarctic Ice Smentioning
confidence: 99%
“…All climate model parameter sets yield climate simulations in agreement with observations over the past 500 years (Loutre et al, 2011). Model parameter set P22 is chosen for the multi-millennial integrations because of its mid-range contribution to sea-level at 2100 AD and 2300 AD in comparison with recent studies Calov et al, 2018;Bulthuis et al, 2019; Tables S1-S2 and Figure S1). The mean annual temperature anomalies over the ice sheets for 2070-2100 relative to 1970-2005 (+4.6˚C over Greenland and +3.8 ˚C over Antarctica for 120 RCP8.5) correspond well with the mid to upper ranges of AOGCM projections over the polar regions (Fettweis et al, 2013, Barthel et al, 2019.…”
Section: Model Description and Initialisationmentioning
confidence: 83%
“…In an ill-conditioned problem, the sensitivity at the surface to perturbations at the base is low. This matrix can also be used to quantify the uncertainty in the ice flow due to uncertainties in the model parameters (see, e.g., Bulthuis et al, 2019;Schlegel et al, 2018;Smith, 2014). Perturbations at the ice base with short wavelength are propagated to the surface with a weaker effect on the height and velocity compared to long wavelengths in Gudmundsson (2003Gudmundsson ( , 2008.…”
Section: G Cheng and P Lötstedt: Sensitivity Analysis Of Ice Sheetmentioning
confidence: 99%
“…The FS equations are solved using Elmer/Ice version 8.4 (rev. f6bfdc9) with the scripts at: https://doi.org/10.5281/zenodo.3611158 (Cheng, 2020a). The forward and adjoint SSA solvers are implemented in MATLAB.…”
Section: A1 the Forward Steady-state Ssa Solutionmentioning
confidence: 99%